Board Game Design as Education to Prevent Game Addiction for Elementary Students - Alifia Ananda Putri; Handriyotopo Handriyotopo (Dinasti International Journal of Education Management And Social Science, 2024)
Child gaming addiction is a type of addiction that many children experience but its existence is rarely known or realized. The use of excessive digital games has several bad effects such as addiction, poor eye health, or lack of socialization in children. However, the nature of children playing games cannot be simply eliminated, so it needs to be completed with the right media. Board game is one of the right medium and with the right visual elements and game mechanics it can be an effective solution. This will be also accompanied by context and material about game addiction education. The method used is the graphic design process method by Robin Landa, the method stages are orientation, analysis and strategy, conceptual design, design development, and implementation. Data was obtained through interviews and questionnaires with elementary students, parents and academics. The design produces an educational board game with the title "Mencari Bintang" with a game mechanism like the classic monopoly board game and also effectiveness test result of the product